Language dynamism in English-Northern Sotho/Northern Sotho-English bilingual dictionaries : a case of translation equivalence - Meso, Tlou Phestus (University of Limpopo, 2016)
This study reveals that language dynamisms affect the compilation of Northern Sotho – English bilingual dictionaries. In this regard, the study shows that the role of translation equivalence cannot be taken for granted. To fully grasp what translation equivalence entails, the study compared formal equivalence with dynamic equivalence. Although there are merits in adopting foreign terms and concepts, the study investigates the problem lexicographers and terminologists of English–Northern Sotho or Northern Sotho–English bilingual dictionaries encounter and suggests possible solutions. Different strategies and procedures for dealing with non-equivalence between the source and target languages are also discussed. Lastly, the study recommends that language dynamism is inevitable if Northern Sotho is to thrive as one of the functional languages in the world. The consequences of shunning dynamism are dire as this might lead to language death.
Thesis (M. A. (Translation and Linguistics)) -- University of Limpopo, 2016
Keywords: Bilingual dictionaries; Bilingualism; English -- Sotho dictionaries